The problem of compatibility between the financial accounting system and IAS (41) in the accounting processing of plant biological assets -comparative analytical study- - rebahi, sabrina (Journal of Research in Finance and Accounting, 2022)
This research study aims to highlight the accounting processing of plant biological assets in accordance with the Financial Accounting System and IAS No. 41, in order to determine the extent to which the accounting system adopts the foundations and principles stipulated in IAS 41, and to highlight the similarities and differences between them. One of the most important finding is that IAS41 detailed the basis of bioactivity accounting, and considered plant biological products as non-current assets for long-term economic periods, taking into account their potential for damage, while the financial accounting system did not provide a comprehensive explanation with regard to the accounting treatment of agricultural products as non-current assets, as they were processed as stocks consumed for agricultural products Sold.